The Effect Of Good Corporate Governance On The Financial Performance Of Banking Companies Listed On The Indonesia Stock Exchange - Yusrani Familiy, Achmad Yurifani; Handayani, Susi; Mohd Ali, Mazurina (International Economic Conference of Business and Accounting, 2024)
This study aims to analyze the influence of Good Corporate Governance (GCG) on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX). GCG problems have increased again with the disclosure of the PT Lippo Bank Tbk scandal case which manipulated financial reports, this proves that the implementation of Good Corporate Governance is still weak even though it has moved away from the monetary crisis period (Sukamulja, 2005). This research uses a type of quantitative research using historical data from banking companies listed on the IDX during the 2020-2022 period. The independent variables in this study include institutional ownership, managerial ownership, and independent commissioners. While the dependent variable is financial performance as measured by Return On Assets (ROA). The results of multiple linear regression analysis show that there is a positive influence of Good Corporate Governance on the financial performance of banking companies. High institutional ownership, strong managerial ownership, and effective independent commissioners positively contribute to good financial performance. The results of this study have important implications for practitioners, regulators and investors in understanding the importance of implementing good GCG in banking companies. Strong GCG implementation can improve the financial performance of banking companies and assist in reducing financial risks. This research also contributes to the literature on GCG and the financial performance of banking companies in Indonesia, and provides a basis for further research in a broader context.